Design of Asset Management Application at SMK Kartika 2 Surabaya - Putranto, Oky; ., Ayuningtyas; Arrosyidi, Achmad (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
SMK Kartika 2 Surabaya with a total of 664 students divided into 4 majors, namely majoring in multimedia, light vehicle engineering, audio video techniques, and banking. Light vehicle engineering and audio engineering video have difficulties in asset management, such as borrowing, returns, and maintenance of goods. The staff still uses the logbook that must be filled by the students. The tool man also does not provide receipts for the items borrowed by the students, therefore, making it difficult to track the availability and viability of the goods. In the process of generating the report, the tool man has difficulties in reporting quantities, specifications, clarifications, and feasibility of certain asset items.Based on the above description of the problem, an asset management application was built, which can assist the head of facilities and infrastructure, the tool man, and students in lending, return and maintenance of goods. This application can help Tool man, in the process of creating reports, reduce the loss of goods and simplify the control of goods.From the asset management test results can generate lending reports, return reports, best-selling assets, as well as a list of assets, employees, and students. Keywords: Website, SMK Kartika 2 Surabaya, Asset Management.